2021
DOI: 10.1016/j.amjmed.2020.12.017
|View full text |Cite
|
Sign up to set email alerts
|

Fish Consumption and Cardiovascular Health: A Systematic Review

Abstract: Studies evaluating fish consumption and cardiovascular disease events have shown inconsistent results. We performed a systematic review of peer-reviewed publications from an extensive query of Ovid MEDLINE, Ovid Embase, Ovid Cochrane Database of Systematic Reviews, Scopus, and Web of Science from database inception to September 2020 for observational studies that reported the association between fish consumption and cardiovascular disease events. We identified and reviewed 24 studies related to fish consumptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 53 publications
(28 reference statements)
1
24
0
1
Order By: Relevance
“…While most of the included studies adjusted for age and sex, many studies did not account for smoking status. Fish consumption is also an important potential confounder, as certain metals and metal species such as Hg and arsenobetaine are abundant in fish and seafood [ 79 ], and fish also contain essential nutrients that may reduce the risk of CVDs [ 80 , 81 ]. Sensitivity analyses restricting to non-fish consumers are therefore important for studies assessing the cardiotoxicity of metal mixtures, especially when arsenic and mercury are being evaluated [ 82 ].…”
Section: Resultsmentioning
confidence: 99%
“…While most of the included studies adjusted for age and sex, many studies did not account for smoking status. Fish consumption is also an important potential confounder, as certain metals and metal species such as Hg and arsenobetaine are abundant in fish and seafood [ 79 ], and fish also contain essential nutrients that may reduce the risk of CVDs [ 80 , 81 ]. Sensitivity analyses restricting to non-fish consumers are therefore important for studies assessing the cardiotoxicity of metal mixtures, especially when arsenic and mercury are being evaluated [ 82 ].…”
Section: Resultsmentioning
confidence: 99%
“…In the present study, the amount of seafood consumption in Prinzmetal angina patients was lower than healthy people. Based on other studies, more intake of fresh fish is a protective factor against cardiovascular diseases [ 50 , 51 ], but some studies have shown inconsistent results. Krittanawong et al [ 50 ], in a review study, concluded that non-fried fish consumption was probably associated with a reduced risk of overall cardiovascular disease events and myocardial infarction risk.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of fish, the method of their cooking is very important. Eating fish can reduce the incidence of cardiovascular disease but eating fried fish can increase the risk of cardiovascular events [ 36 , 37 ]. In Poland, it is particularly important to include fish in food-based dietary guidelines due to very low consumption in this country [ 27 , 38 ].…”
Section: Discussionmentioning
confidence: 99%